METODOLOGI TAFSIR IMAM AL-SHAWKÃNÃ DALAM KITAB FATH AL-QADÃR: KAJIAN TERHADAP SURAH AL-FÃTIHAH - Ihsan, Muhammad (Hunafa: Jurnal Studia Islamika, 2008)
This research aims to describe the interpretive methodology of ImÃ¢m al-ShawkÃ¢nÃ® in his Fath al-QadÃ®r. The focus of this reseach is on the method, technique and sources which are employed by Â Al-ShawkÃ¢nÃ® in his interpretation of sÃ»rat al-FÃ¢tihah. This is carried out, first of all, through the reading of the sÃ»rah and its analysis through identification and classification. The research shows that the method employed in interpreting the sÃ»rah is tahÃ®lÃ® method, which is based on the text of the Quran, hadÃ®th, scholars opinions including sahÃ¢bah and tÃ¢biâÃ®n. Furthermore, in terms of the technique of interpretation, Al-ShawkÃ¢nÃ® used textual, systemic, linguistic, cultural and logical techniques of interpretation.Kata Kunci : metodologi tafsir, kitab Fath al-QadÃ®r, tafsÃ®r bi al-maâthÃ»r, Â Â metode tahlÃ®lÃ®, metode maudÃ»âÃ®